Staged repair of redo and crippled hypospadias: analysis of outcomes and complications. Issue 2 (April 2019) - Badawy, H.; Soliman, A.; Moussa, A.; Youssef, M.; Fahmy, A.; Dawood, W.; Elmesiry, M.; Assem, A.; Elsayed, S.; Abulfotooh Eid, A.; Orabi, S.
Summary: Introduction: Residual curvature, scarred or absent urethral plate, shortage of skin, and paucity of vascularized tissues and flaps are all obstacles to overcome during repair of redo and cripple hypospadias after failed reconstruction. Limited articles address the outcome of repair of these cases using different grafts. Objective: An analysis of outcomes and complications after the repair of redo and cripple hypospadias in a cohort of children operated by a single surgeon is presented, and data are retrieved from a prospectively designed database. Study design: Thirty-one children with a median age of 96 months (18–216, interquartile range [IQR]: 78), who underwent previous surgeries three to five times, were operated in the period from late 2011 to August 2017 in a single center by a single surgeon (first author); the first-stage repair was performed by using an inner prepuce graft in three children and oral grafts in 28 children. Penile straightening by degloving and removal of ventral scarred tissues are followed by development of glanular wings and grafting of the ventral surface. Results: Eleven distal penile hypospadias and 20 posterior hypospadias were operated. First-stage repair was revised in three children; 25 children, eight distal and 17 posterior hypospadias, underwent second-stage repair with a median age of 84 months (18–216, IQR: 60). The success rate after the second-stage repair was 56% (14 children), and complications were encountered in 11 children in the form of penoscrotal fistulae in four, complete dehiscence in one, and glanular dehiscence in six children. After closure of fistulae, the overall success rate increased to 72%. Although complications were more common among children with posterior hypospadias (nine children) than children with distal hypospadias (two children), no statistical significance was reached (p = .234), with no effect of age on complications (p = .233), no effect of the position of the meatus on glanular dehiscence (p = .624), and no effect of age on glanular dehiscence (p = .114). Conclusion: Repair of redo and crippled hypospadias using staged graft repair in children could be achieved with a satisfactory overall success rate of 72%. Glanular dehiscence is the main complication; however, it is not considered by parents of children in the series, necessitating intervention. The lowest complication rate is expected among those with a position of the meatus more distal, however, not proven statistically in the series.Image 1